PENILAIAN KERUSAKAN DAN KEHILANGAN LAHAN KOPI PASCAERUPSI GUNUNGAPI MERAPI 2010 - , DINAR APRIYANTO, Prof. Dr. Sunarto, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The 2010 Merapi eruption has brought a quite significant effect upon the regions surrounding Merapi slopes. This study is aimed to estimate the damage and lost of coffee plantations as one of the superior commodities in Merapi region which was affected by Merapi eruption. This study was conducted in three villages